2008
DOI: 10.1103/physrevb.77.125106
|View full text |Cite
|
Sign up to set email alerts
|

Importance oft2geghybridization in transition metal oxides

Abstract: The crucial importance of the t 2g -e g hybridization in transition metal oxides

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 19 publications
5
51
2
Order By: Relevance
“…The e ge g couplings, for instance, were found to be important in trigonally distorted 3d 5 compounds. 52 Our data in Table II, showing that with trigonal distortions the a 1g -e g splittings decrease (as∆ <∆ 0 ), qualitatively confirm the quantum chemistry results of Landron and Lepetit, i.e., in the presence of trigonal squashing the e g levels are energetically favored as compared to the a 1g states, in contrast to naive expectations based on one-electron crystal-field theory. Obviously, for 5d oxides, the t 2g -e g couplings are further enhanced by the strong SOI's.…”
supporting
confidence: 86%
“…The e ge g couplings, for instance, were found to be important in trigonally distorted 3d 5 compounds. 52 Our data in Table II, showing that with trigonal distortions the a 1g -e g splittings decrease (as∆ <∆ 0 ), qualitatively confirm the quantum chemistry results of Landron and Lepetit, i.e., in the presence of trigonal squashing the e g levels are energetically favored as compared to the a 1g states, in contrast to naive expectations based on one-electron crystal-field theory. Obviously, for 5d oxides, the t 2g -e g couplings are further enhanced by the strong SOI's.…”
supporting
confidence: 86%
“…The same angle change can also be seen in RCrO 3 . Landron and Lepetit 19 have shown that the intrasite hybridization between t and e orbitals is highly sensitive to the angle ␤ ͑they have defined the trigonal distortion of an octahedron by a different angle͒. In our case, the intrasite t-e hybridization vanishes for ␤ = 90°.…”
Section: Resultsmentioning
confidence: 53%
“…6, we show the ∆-dependence of T c at U = 4 and 6 eV for unhydrate and hydrate systems, respectively. Note that the cluster calculation using quantum chemical ab-initio methods suggests U = 4.1 ∼ 4.8 eV [34]. In both cases, T c is almost zero if we drop shear phonons (b 1 = b 2 = 0).…”
Section: Numerical Resultsmentioning
confidence: 89%
“…Here, we regard ∆ as variable. Equations (33) and (34) are shown in Fig. 4 (a) and (b), respectively.…”
Section: Derivation Of Gap Equationmentioning
confidence: 99%